The Effect of Ethics-Oriented Leadership and Political Skills of Digital Organizational Developments on Accounting Students' Perceptions - Samira Zare Asl; Mohammad Kiamehr (International Journal of Digital Content Management, 2023)
Purpose: The purpose of this study was to investigate the effect of ethics-oriented leadership and political skills of digital organizational developments on accounting students' perceptions. Method: The study population in this study was accounting students in Shiraz. The statistical population of this study includes all accounting students in Shiraz, whose number is 850 people. The number of samples was 265 based on the Morgan table. 400 questionnaires were distributed electronically and randomly and 265 questionnaires were selected. After data collection, structural equations were analyzed using SPSS and SMART PLS software. Findings: Based on the results, ethical leadership has a positive and significant relationship with accounting students' perception of leadership effectiveness. Political skills have a negative and significant relationship with accounting students' perception of leadership effectiveness. Machiavellianism mediates the role of leadership in the relationship between ethical leadership and accounting students' perceptions of leadership effectiveness. Machiavellianism has an increasing mediating role in political skills and accounting students' perceptions of leadership effectiveness. Conclusion: This article is practical. Therefore, its main contribution is to clarify the discussion about the impact of digital transformation in the accounting sector and the importance of accounting ethics in the digital age. Nevertheless, the results can be interesting for researchers, policymakers, teachers, professional institutions, and accounting professionals.